Income-Related Inequalities in Chronic Disease Situation Among the Chinese Population Aged Above 45 Years - Qin Shangren PhD; Huang Zirui BS; Ding Ye MS (SAGE Publishing, 2019)
There is relatively little published on the socioeconomic distribution of chronic disease burden in older people. This study aims to quantify income-related inequalities in chronic disease situation among ≥45-year-old people in China. Data were collected from the 2015 China Health and Retirement Longitudinal Study. Self-reported chronic conditions included 14 diseases (ie, heart problem, diabetes). Multivariate Generalized Quasi-Poisson Regression was used to evaluate associations between prevalence and personal income. Prevalence of hypertension was highest among people above ≥ 75 (male participants 44.41%, female participants 47.53%). Heart problem prevalence increased with age. Chronic disease prevalence among population aged 45 to 59 years was greatly affected by income. Prevalence ratios (PRs) were highest for heart problems in 45 to 59 middle-income male participants and for memory-related diseases in 45 to 59 middle-income female participants. Significant inequalities in chronic conditions prevalence persist into old age, particularly among 45- to 59-year-old people. Opposite to developed countries, the prevalence of some chronic disease (ie, heart problem) is higher in richer populations in China. These findings pose the policy challenge of needing to prevent such inequalities in older years.